The 2021 International Society for the Study of Hypertension in Pregnancy classification, diagnosis & management recommendations for international practice - Magee, Laura A; Brown, Mark A.; Hall, David R.; Gupte, Sanjay; Hennessy, Annemarie; Karumanchi, S. Ananth; Kenny, Louise C.; McCarthy, Fergus; Myers, Jenny; Poon, Liona C.; Rana, Sarosh; Saito, Shigeru; et al. (Pregnancy hypertension, 2022)
•This updates the 2018 ISSHP guidelines, and feedback is invited (info@isshp.org).•Angiogenic imbalance is uteroplacental dysfunction when definingpre-eclampsia.•Use multivariable models to estimate the risk of developing pre-eclampsia.•Use aspirin from early pregnancy to halve the risk of preterm pre-eclampsia.•Use multivariable models to estimate the risk of pre-eclampsia complications.•Treat hypertension to a target diastolic BP of 85 mmHg, before or after birth. All units managing hypertensive pregnant women should maintain and review uniform departmental management protocols and conduct regular audits of maternal & fetal outcomes. The cause(s) of pre-eclampsia and the optimal clinical management of the hypertensive disorders of pregnancy remain uncertain; therefore, we recommend that every hypertensive pregnant woman be offered an opportunity to participate in research, clinical trials and follow-up studies.